2015
DOI: 10.1068/a140194p
|View full text |Cite
|
Sign up to set email alerts
|

Markets, Nature, Neoliberalism, and Conservation through Private Protected Areas in Southern Chile

Abstract: A vibrant literature has emerged in recent years exploring moves towards neoliberal forms of conservation, with a reduced role for the state and an enhanced role for markets and private and civil society actors. Yet there is a need for studies which explore how and why this trend has emerged, and what impact it has on both people and nature. The author provides a detailed examination of private protected areas, which are often associated with neoliberal approaches to conservation, in Chile—a country which has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(27 citation statements)
references
References 43 publications
0
25
0
2
Order By: Relevance
“…Alderman dealt with the Within their studies of Biosphere Reserves and the Regional Geography of Colombia, Borsdorf, Marchant and others adressed the topic of privately owned protected areas and discussed their legal status (Borsdorf 2011; Borsdorf & Mergili 2011;Borsdorf et al 2011;Borsdorf et al 2013;Borsdorf & Marchant 2013a, b;Marchant & Borsdorf 2013;Borsdorf 2016). Initial overviews of the Chilean experience ware given by Sepúlveda and García (1997), Maldonado (1999), and Holmes (2014Holmes ( , 2015. Hora and Marchant (2015) showed how a private park (the Oncol Park) may support the local economy; Sánchez (2016) demonstrated the value of a community-owned protected area to protect ancestral lands.…”
Section: State-of-the-artmentioning
confidence: 99%
See 1 more Smart Citation
“…Alderman dealt with the Within their studies of Biosphere Reserves and the Regional Geography of Colombia, Borsdorf, Marchant and others adressed the topic of privately owned protected areas and discussed their legal status (Borsdorf 2011; Borsdorf & Mergili 2011;Borsdorf et al 2011;Borsdorf et al 2013;Borsdorf & Marchant 2013a, b;Marchant & Borsdorf 2013;Borsdorf 2016). Initial overviews of the Chilean experience ware given by Sepúlveda and García (1997), Maldonado (1999), and Holmes (2014Holmes ( , 2015. Hora and Marchant (2015) showed how a private park (the Oncol Park) may support the local economy; Sánchez (2016) demonstrated the value of a community-owned protected area to protect ancestral lands.…”
Section: State-of-the-artmentioning
confidence: 99%
“…Traditionally nature protection, conservation and regional development have been the concern of public authorities , as normally the implementation of protected areas needed public financing and was not regarded as a business. However, the privatization trend reached nature conservation in the late 1980s (Holmes 2015). In many countries, private actors declared land as a protected area, bought land to create such sites, or even took over the control of former national parks.…”
Section: Introductionmentioning
confidence: 99%
“…Basta ver la política ambiental de la multinacional ARAUCO que incluye: i) no deforestar el bosque nativo que posee y establecer modelos de áreas protegidas privadas (e.g. Parque Oncol), tema que ha sido tratado con relación a los acaparamientos verdes y las reservas privadas como formas de apropiar la naturaleza (Holmes, 2015); y ii) realizar una actividad forestal 'certificada y sostenible', mediante eco-etiquetado certificado por empresas independientes como FSC (ARAUCO, s.f.). El tema de las certificaciones ha recibido bastante atención igualmente.…”
Section: El Discurso Y La Praxis Del Crecimiento Verdeunclassified
“…the Douglas Tompkins’ Pumalín Park in Chile. Community and private parks are, however, also exposed to risks such as a change of ownership, social-environmental conflicts and issues inherent to the tragedy of the commons (Holmes 2014, 2015). A recent analysis has shown that all types of area protection are powerful when applied in a regional mix of approaches (Leménager et al 2014).…”
Section: The Need To Incorporate Aze Sites Into the Protected Areas Nmentioning
confidence: 99%